Applied numerical methods with Python for engineers and scientists - Chapra, Steven C.; Clough, David E. (McGraw Hill LLC, 2022)
"When we first learned to use computers as students in the 1960s, Fortran was the language of choice for most engineering and scientific computations. Over the ensuing half century, numerous other languages have proven useful for implementing the numerical calculations that are so valuable to our research and teaching. Along with a succession of improved Fortran versions, other languages such as Algol, Basic, Pascal, and C/C++ have all found their way into our computational toolbox. The basic content, organization, and pedagogy of this book is like our other numerical methods textbooks. In particular, a conversational writing style is intentionally maintained in order to make the book easier to read. This book tries to speak directly to the reader and is designed in part to be a tool for self-teaching. As such, we also believe it will have value outside the classroom for professionals desiring to gain proficiency in both numerical methods and Python"--Provided by publisher.